Pemberian Kompensasi atas Gangguan Layanan dalam Aplikasi M-Paspor: Analisis Hukum Berdasarkan Peraturan Menteri Hukum dan HAM Nomor 8 Tahun 2014 tentang Paspor Biasa dan Surat Perjalanan Laksana Paspor - Sartio, Dessy Octavina Sumala; Nugroho, Any; Noor, Syamhudian (FOCUS, 2025)
This study aims to analyze the compensation mechanism for service disruptions in the M-Paspor application and the government's responsibility in addressing the legal vacuum (rechtsvacuum) in digital immigration services. The research employs a normative juridical method with a statutory approach, utilizing primary, secondary, and tertiary legal sources. The study focuses on immigration service regulations and case studies of technical issues in the M-Paspor application. Data collection is conducted through document analysis and legal interpretation to assess the adequacy of existing regulations. The findings indicate that no specific legal norms currently regulate compensation for users affected by service disruptions, creating uncertainty and potential financial losses. The government holds legal and administrative responsibility to address this gap through additional regulations and policy alignment with higher legal frameworks. A more comprehensive regulatory framework is necessary to ensure legal certainty and fair protection for the public while improving the quality and reliability of digital immigration services.